Removal of Microplastics and Performance of a Developed Ceramic Filter - Vogel, Natália; Pedrotti, Matheus; Zimmer, André (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2024)
The consumption of microplastics can have harmful effects. To effectively remove microplastics from water using an affordable device, this study developed a ceramic filter based on clay and waste glass. The research evaluated the addition of a porogenic agent and the effects of firing temperature. In the formulations, clay was substituted by a porogenic agent with 10 and 20 by weight, maintaining 10 by weight of waste glass. Ceramic filters were produced by molding press, and evaluated for their physical properties. Its performance was assessed by water permeability at different pressures, leaching of elements, and removal of microplastics. As a result, formulations with a higher porogenic agent content and lower firing temperature present superior permeability, however, permeability increases after higher pressure tests, when structure fracture may occur. Moreover, the formulation with the lowest porosity (without adding a porogenic agent) achieved an impressive removal rate of nearly 99.8%. It was concluded that a ceramic filter could retain microplastics well, as long as the filtration pressure and porosity were optimized to obtain the best results – higher filtration without fracture.